Considering Age-Related Hearing Loss in Neuropsychological Practice: Findings from a Feasibility Study. Issue 2 (7th December 2018) - Dupuis, Kate; Yusupov, Iris; Vandermorris, Susan; Murphy, Kelly L.; Rewilak, Dmytro; Stokes, Kathryn A.; Reed, Marilyn
RÉSUMÉ: La perte auditive représente une problématique répandue chez la population âgée. Cela peut poser des défis pour les neuropsychologues, étant donné que les méthodes d'intervention doivent être présentées oralement et donc entendues avec précision. Dans cette étude, le statut auditif de 20 clients (âge moyen= 71 ans) a été évalué au sein d'une clinique de neuropsychologie en milieu hospitalier et l'impact de cette évaluation sur la pratique des neuropsychologues a été étudié. Un assistant de recherche a administré un bref test de dépistage des troubles auditifs à chacun des clients. Nous avons demandé à quatre neuropsychologues de commenter le statut auditif de leurs clients avant et après leur avoir présenté les résultats des tests de dépistage. Le dépistage a révélé que la majorité des clients présentait au moins une perte auditive légère et que les neuropsychologues étaient relativement précis (60 %) dans leur estimation du statut auditif de leurs clients. Enfin, les neuropsychologues ont utilisé l'information sur le statut auditif de leurs clients en vue de les diriger vers des services en audiologie, ainsi que pour renseigner les clients et les familles sur la perte auditive et la communication. ABSTRACT: Hearing loss is highly prevalent in older adults and can pose challenges for neuropsychologists, as assessment and intervention procedures often involve orally presented information which must be accurately heard. This project examined the hearing status of 20 clients (mean age = 71 years) in a hospital-based outpatient neuropsychology clinic, and explored whether information about hearing loss informed neuropsychologists' clinical practice. A research assistant administered a brief hearing screening test to each participant. Four treating neuropsychologists were asked to comment on their client's hearing status before and after being shown their client's hearing screen test results. Screening revealed that the majority of participants had at least mild hearing loss, and that the neuropsychologists were relatively accurate (60%) at estimating their clients' hearing status. Neuropsychologists used information about a client's hearing status to make recommendations that clients pursue audiologic services, and to educate clients and family members about hearing loss and communication.